The Degree Of Using Artificial Intelligence Among Academic Leaders In Jordanian Universities And Its Relationship To Teaching Competencies Of Faculty Members (Journal of Namibian Studies : History Politics Culture, 2023)
This study aimed to investigate the degree of use of artificial Intelligence (AI) by academic leaders in Jordanian universities and its relationship to the teaching competencies of faculty members. The descriptive correlation approach was used. A total of (350) faculty members from Jordanian universities participated in the study during the second semester of the academic year 2022/2023. It was found that academic leaders in Jordanian universities use AI to a high degree. In addition, Faculty members' teaching competency was high. The findings yielded a statistically significant positive relationship between the degree of academic leaders' practice of AI  and the level of teaching competencies of faculty members.The researcher recommended that universities adopt the concept of AI because of its positive role in achieving its mission, Vision  , and goals, motivating the faculty members , and developing their teaching competence. The findings yielded a statistically significant positive relationship between the degree of academic leaders' practice of AI  and the level of teaching competencies of faculty members.